2010
DOI: 10.1111/j.1532-5415.2010.03137.x
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Emergency Medical Services–Based Program to Identify and Assist Older Adults in a Rural Community

Abstract: Rural-dwelling older adults experience unique issues related to accessing medical and social services. We describe the development, implementation, and experience of a novel, community-based program to identify rural-dwelling older adults with unmet medical and social needs. The program leveraged the existing emergency medical services (EMS) system. The program specifically included: 1) geriatrics training for EMS providers; 2) screening of older adult EMS patients for falls, depression, and medication managem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(94 citation statements)
references
References 17 publications
1
93
0
Order By: Relevance
“…Indeed, others have identified limited education in this area at the entry to practice and ongoing professional development levels, 11 and the need for further or better training to improve accuracy or appropriateness in referral programs 3 and screening. 5 Another salient theme emerging from the data was the strong desire by paramedics to receive meaningful feedback and improve communication regarding referrals made. In cases where feedback lacked detail or was delayed it did little to improve paramedics' use or understanding of the CREMS program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, others have identified limited education in this area at the entry to practice and ongoing professional development levels, 11 and the need for further or better training to improve accuracy or appropriateness in referral programs 3 and screening. 5 Another salient theme emerging from the data was the strong desire by paramedics to receive meaningful feedback and improve communication regarding referrals made. In cases where feedback lacked detail or was delayed it did little to improve paramedics' use or understanding of the CREMS program.…”
Section: Discussionmentioning
confidence: 99%
“…3 Paramedics have demonstrated capacity in identifying individuals at risk of deterioration in the home. 4,5 As such, the paramedic community has developed, implemented, and continues to expand programs involving paramedics initiating referrals to community services (referred to as "community referrals by EMS (Emergency Medical Services)" or "CREMS"). Referral programs aim to promote the health and quality-of-life of seniors, improve their access to resources, and reduce 911-system activations and hospital visits.…”
Section: Introductionmentioning
confidence: 99%
“…Our review of titles and abstracts suggested that 138 articles might be eligible. After studying full texts, we confirmed that 13 papers 61,62,66,80,[89][90][91][92][93][94][95][96][97] reporting 12 studies met our inclusion criteria, as detailed in Figure 1. Table 4 summarises the 12 included studies; Tables 5 and 6 describe them in more detail and Table 7 assesses their quality.…”
Section: Inclusionmentioning
confidence: 56%
“…Of the 12 studies, six 61,62,66,80,89,94 came from the UK, four [90][91][92][93] came from the USA, one 97 came from Australia and one 95 came from New Zealand. Study designs comprised two RCTs 61,66 (one of which 61 published a separate paper evaluating cost-effectiveness element of the study), 62 nine cohort studies (of which six did not include a comparator arm 89,[91][92][93]95,97 and three included intervention and control arms 80,90,96 ) and one qualitative study.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation